2007
DOI: 10.1073/pnas.0701652104
|View full text |Cite
|
Sign up to set email alerts
|

The neoselectionist theory of genome evolution

Abstract: The vertebrate genome is a mosaic of GC-poor and GC-rich isochores, megabase-sized DNA regions of fairly homogeneous base composition that differ in relative amount, gene density, gene expression, replication timing, and recombination frequency. At the emergence of warm-blooded vertebrates, the gene-rich, moderately GC-rich isochores of the cold-blooded ancestors underwent a GC increase. This increase was similar in mammals and birds and was maintained during the evolution of mammalian and avian orders. Neithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
99
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 93 publications
4
99
0
2
Order By: Relevance
“…These changes are inherited Mendelianly, Lamarckly or otherwise; mutations are acquired and inherited transmitted (Lamarck); the influence of a base in the velocity of replication or transcription is not necessarily Mendelian, nor Lamarckian. High non-random internucleotide interactions are then expected as they were found in Bernardi's isochors (Bernardi, 1993(Bernardi, , 2007) and Karlin's signatures (Karlin and Mrazek, 1997). We found strong interactions among the nucleotides of a dinucleotide when they were separated by 0 (consecutive), 1, 2 … K nucleotide sites (Valenzuela, 2009(Valenzuela, , 2010(Valenzuela, , 2011(Valenzuela, , 2012Valenzuela et al, 2010).…”
Section: Interactions and Periodicities Of Nucleotidesmentioning
confidence: 73%
See 1 more Smart Citation
“…These changes are inherited Mendelianly, Lamarckly or otherwise; mutations are acquired and inherited transmitted (Lamarck); the influence of a base in the velocity of replication or transcription is not necessarily Mendelian, nor Lamarckian. High non-random internucleotide interactions are then expected as they were found in Bernardi's isochors (Bernardi, 1993(Bernardi, , 2007) and Karlin's signatures (Karlin and Mrazek, 1997). We found strong interactions among the nucleotides of a dinucleotide when they were separated by 0 (consecutive), 1, 2 … K nucleotide sites (Valenzuela, 2009(Valenzuela, , 2010(Valenzuela, , 2011(Valenzuela, , 2012Valenzuela et al, 2010).…”
Section: Interactions and Periodicities Of Nucleotidesmentioning
confidence: 73%
“…The previous analyses and Table 6 show that at any site there is a resilient equilibrium of base frequencies co-adapted to their residual genome, where each site is in turn in a resilient equilibrium, in a tense dynamic process of turnover adapted to environmental conditions. The genome is also an integrated phenotype (Bernardi, 2007). This tense dynamic system is exquisitely sensitive to environmental changes.…”
Section: Interactions and Periodicities Of Nucleotidesmentioning
confidence: 99%
“…In bacteria, for example, an increase in GC content correlates with a higher temperature optimum and a broader tolerance range for a species (21,22). Selection for higher thermal stability has also been suggested to explain the evolution of GC-rich regions in the genomes of homeothermic vertebrates in contrast to their GCpoor homologs found in poikilothermic (i.e., cold-blooded) groups, such as fish and amphibians (9). Nevertheless, other alternative hypotheses have also been proposed to explain GC richness in bacteria and certain regions of vertebrate genomes (7,8,11,23,24).…”
mentioning
confidence: 99%
“…In prokaryotes, the GC content is a well-studied and widely used character in taxonomy (3), and numerous studies have shown both the impact of GC content on microbial ecology and the influence of the environment in shaping the DNA base composition of microbial communities (4)(5)(6)(7). The DNA base composition is also frequently discussed in relation to the evolution of the isochore structure in humans and other homeothermic (warm-blooded) vertebrates (i.e., birds and mammals) (8)(9)(10). In contrast, considerably less attention has been paid to the biological relevance of genomic GC content variation in plants (11), with genomic GC contents known only for a limited amount of the total phylogenetic diversity (11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Whereas one chromosome is suspected to have been acquired by horizontal transfer, the other one is proposed to be a sex-determining chromosome. The genomes of mammals and other vertebrates have long been known to be mosaics of isochores of GC-rich and GC-poor regions longer than 300 kb (Macaya et al 1976), correlated with strong biases in gene density or repeated sequences, and with some biases in gene expression, replication timing, and recombination (Bernardi 2007). In the above examples, the GC-content heterogeneity is explained by specific chromosomal organization or genetic content.…”
mentioning
confidence: 99%